The art of bringing extinction to a freeze - History and future of species conservation - Thomas Hildebrandt; Susanne Holtze; Muhammad Agil; Pierfrancesco Biasetti; Julia Bohner; Miguel Casares; Loles Carbonell; Silvia Colleoni; Hayden Cuthill; Barbara De Mori; Sebastian Diecke; Cesare Galli; et al. (Cryobiology, 2025)

Ant invasion is associated with lower root density and different root distribution of a foundational savanna tree species - Patrick D. Milligan; Todd M. Palmer; John S. Lemboi; John Mosiany; Samuel Mutisya; Benard Gituku; Alfred Kibungei; Elizabeth G. Pringle (Biological Invasions, 2023)

Application of decision tools to ethical analysis in biodiversity conservation - Pierfrancesco Biasetti; Thomas B. Hildebrandt; Frank Göritz; Robert Hermes; Susanne Holtze; Jan Stejskal; Cesare Galli; Ilaria Pollastri; Alessia Muzzo; Isaac Lekolool; David Ndereeh; Patrick Omondi; et al. (Conservation Biology, 2023)
Achieving ethically responsible decisions is crucial for the success of biodiversity conservation projects. We adapted the ethical matrix, decision tree, and Bateson's cube to assist in the ethical analysis of complex conservation scenarios by structuring these tools so that they can implement the different value dimensions (environmental, social, and animal welfare) involved in conservation ethics. We then applied them to a case study relative to the decision‐making process regarding whether or not to continue collecting biomaterial on the oldest of the two remaining northern white rhinoceroses ( Ceratotherium simum cottoni ), a functionally extinct subspecies of the white rhinoceros. We used the ethical matrix to gather ethical pros and cons and as a starting point for a participatory approach to ethical decision‐making. We used decision trees to compare the different options at stake on the basis of a set of ethical desiderata. We used Bateson's cube to establish a threshold of ethical acceptability and model the results of a simple survey. The application of these tools proved to be pivotal in structuring the decision‐making process and in helping reach a shared, reasoned, and transparent decision on the best option from an ethical point of view among those available.

Demographic consequences of mutualism disruption: Browsing and big‐headed ant invasion drive acacia population declines - Brandon R. Hays; Corinna Riginos; Todd M. Palmer; Daniel F. Doak; Benard C. Gituku; Nelly J. Maiyo; Samuel Mutisya; Simon Musila; Jacob R. Goheen (Ecology, 2022)
Across the globe, biological invasions have disrupted mutualisms, producing reverberating consequences for ecosystems. Although invasive species frequently trigger mutualism disruptions, few studies have quantified the demographic mechanisms by which mutualism breakdown may generate population effects. In a Kenyan savanna, the invasive big‐headed ant ( Pheidole megacephala ) has disrupted a foundational mutualism between the monodominant whistling‐thorn tree ( Acacia drepanolobium ) and native ants ( Crematogaster spp.) that deter browsing by large mammalian herbivores. We conducted experiments to quantify the demographic consequences of this mutualism disruption in the presence and absence of large mammalian herbivores. Invasion by P. megacephala exacerbated population declines of A. drepanolobium , primarily through decreased survival and reproduction of adult trees. However, these fitness reductions were small compared to those resulting from the presence of large mammalian herbivores, which negatively impacted growth and survival. Contrary to expectation, the expulsion of metabolically costly Crematogaster mutualists by P. megacephala did not result in higher population growth rates for trees protected from large mammalian herbivores. Our results suggest that invasive P. megacephala may impose a direct metabolic cost to trees exceeding that of native mutualists while providing no protection from browsing by large mammalian herbivores. Across landscapes, we expect that invasion by P. megacephala will reduce A. drepanolobium populations, but that the magnitude and demographic pathways of this effect will hinge on the presence and abundance of browsers.

Frenemy at the gate: Invasion by Pheidole megacephala facilitates a competitively subordinate plant ant in Kenya - Todd M. Palmer; Corinna Riginos; Patrick D. Milligan; Brandon R. Hays; Alejandro G. Pietrek; Nelly J. Maiyo; Samuel Mutisya; Benard Gituku; Simon Musila; Scott Carpenter; Jacob R. Goheen (Ecology, 2021)
Biological invasions can lead to the reassembly of communities and understanding and predicting the impacts of exotic species on community structure and functioning are a key challenge in ecology. We investigated the impact of a predatory species of invasive ant, Pheidole megacephala , on the structure and function of a foundational mutualism between Acacia drepanolobium and its associated acacia‐ant community in an East African savanna. Invasion by P. megacephala was associated with the extirpation of three extrafloral nectar‐dependent Crematogaster acacia ant species and strong increases in the abundance of a competitively subordinate and locally rare acacia ant species, Tetraponera penzigi , which does not depend on host plant nectar. Using a combination of long‐term monitoring of invasion dynamics, observations and experiments, we demonstrate that P. megacephala directly and indirectly facilitates T. penzigi by reducing the abundance of T. penzigi ’s competitors ( Crematogaster spp.), imposing recruitment limitation on these competitors, and generating a landscape of low‐reward host plants that favor colonization and establishment by the strongly dispersing T. penzigi . Seasonal variation in use of host plants by P. megacephala may further increase the persistence of T. penzigi colonies in invaded habitat. The persistence of the T. penzigi–A. drepanolobium symbiosis in invaded areas afforded host plants some protection against herbivory by elephants ( Loxodonta africana ), a key browser that reduces tree cover. However, elephant damage on T. penzigi ‐occupied trees was higher in invaded than in uninvaded areas, likely owing to reduced T. penzigi colony size in invaded habitats. Our results reveal the mechanisms underlying the disruption of this mutualism and suggest that P. megacephala invasion may drive long‐term declines in tree cover, despite the partial persistence of the ant–acacia symbiosis in invaded areas.